ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA CV. SIAK SEJAHTERA PERIODE 2010 s/d 2014 - Zega, Herianto Zega; Johan, Rina Selva Johan Selva; Riadi, RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Assessment of the financial performance of a company can be done by analyzing the company's financial statements. Financial statements describe the development of the company's financial performance in a particular period. The company's financial performance can be measured by using financial ratio analysis. This study aims to determine the financial performance of CV. Siak Sejahtera based on analysis of liquidity ratio, solvency and profitability ratios. The analytical method used is descriptive quantitative method. The results based on the ratio of the overall liquidity of the year 2010 - 2014 show a good performance or liquid because liquid assets available able to guarantee the current liabilities of the company. The company's solvency ratio from year 2010 - 2014 as a whole is in a position solvable because the assets and capital of the company is able to guarantee the debts or obligations. While the profitability ratios of the year 2010 - 2014 as a whole shows the state of the company at unfavorable position because during the period of the last five years is below the standard ratio. Keywords: Financial Statements, Financial Performance, Financial Ratios